2016
DOI: 10.1016/j.yexcr.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

MAGP2 controls Notch via interactions with RGD binding integrins: Identification of a novel ECM–integrin–Notch signaling axis

Abstract: Canonical Notch signaling involves Notch receptor activation via interaction with cell surface bound Notch ligand. Recent findings also indicate that Notch signaling may be modulated by cross-talk with other signaling mechanisms. The ECM protein MAGP2 was previously shown to regulate Notch in a cell type dependent manner, although the molecular details of this interaction have not been dissected. Here, we report that MAGP2 cell type specific control of Notch is independent of individual Notch receptor-ligand c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…Mechanistically, MAGP-2 mediated stimulation of Notch signaling was shown to involve direct binding between the MAGP-2 C-terminal domain, and the EGF-like domains of Notch1 and Jagged1 [31]. In addition, RGD→RGE mutation of the MAGP-2 integrin binding domain converted MAGP-2 from a suppressor to an activator of Notch signaling in endothelial cells suggesting that MAGP-2 may also regulate Notch via interactions with integrins [32]. This finding may help to explain the cell type dependent effects of MAGP-2 on Notch signaling previously observed [33] and suggests that cell type specific control of Notch may be dependent on several factors including integrin and Notch ligand expression profiles.…”
Section: Direct Ecm-notch Interactions That Control Notch Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, MAGP-2 mediated stimulation of Notch signaling was shown to involve direct binding between the MAGP-2 C-terminal domain, and the EGF-like domains of Notch1 and Jagged1 [31]. In addition, RGD→RGE mutation of the MAGP-2 integrin binding domain converted MAGP-2 from a suppressor to an activator of Notch signaling in endothelial cells suggesting that MAGP-2 may also regulate Notch via interactions with integrins [32]. This finding may help to explain the cell type dependent effects of MAGP-2 on Notch signaling previously observed [33] and suggests that cell type specific control of Notch may be dependent on several factors including integrin and Notch ligand expression profiles.…”
Section: Direct Ecm-notch Interactions That Control Notch Signalingmentioning
confidence: 99%
“…Subsequent work showed that EGFL7 control of Notch in endothelial and placental trophoblast cells was important for placenta development and that decreased EGFL7 expression may be linked to preeclampsia [41, 42]. In addition to controlling Notch via direct interaction with Notch receptors, recent work showed that RGD→RGE mutation of the EGFL7 integrin-binding domain enhanced Notch signaling in endothelial cells [32]. By regulating Notch via direct interactions with Notch receptors and via RGD integrin binding, EGFL7 demonstrates similarities with MAGP-2 and suggest that dual control of Notch by ECM molecules is a common theme.…”
Section: Direct Ecm-notch Interactions That Control Notch Signalingmentioning
confidence: 99%
“…Thus, we speculated that MFAP5 may activate NOTCH2 signaling pathway through alternative ways. According to previous studies, MFAP5 interacts with multiple membrane receptors in an RGD‐domain relied manner 34,47 . We further investigated the role of MFAP5 in ligand receptor binding activation of NOTCH2 signaling pathway.…”
Section: Resultsmentioning
confidence: 94%
“…As a soluble factor, EGFL7 would be readily available for either direct interaction with Notch receptors or with lower affinity membrane associated proteins. This hypothesis is fairly well supported by the fact that EGFL7 can directly bind Notch receptors , can interact with the αvβ3 integrin through its—not conserved—RGD motif which is in close proximity to the putative DSL (Delta/Serrate/LAG‐2) domain required for Notch receptor–ligand interaction and that the human EGFL7 RGD domain is also needed to modulate Notch signaling .…”
Section: Discussionmentioning
confidence: 96%